Anticipating Interpretivism: Heclo and Wildavsky as Pioneers?. Issue 3 (September 2014) - Weller, Patrick
<x xml:space="preserve">Abstract</x> The Private Government of Public Money, published by Hugh Heclo and Aaron Wildavsky, was a study of the working of the Treasury in Britain. Even if some of the detail is now dated, their bold and innovative approach, portraying Whitehall as a community, was an antidote to the rather formal descriptions that had been the standard early accounts. This article examines the approach they took, assesses its impact on future studies and asks whether they were pioneering the route for future interpretivist studies. It concluded that even if neither of the authors would have been comfortable to be categorised in those terms, they did open up the study of government in a way that has encouraged and enabled later interpretevist research.